Simultaneously enhancing the strength and plasticity of Ti-based bulk metallic glass composites via microalloying with Ta. Issue 1 (2nd January 2020) - Zhou, Jie; Wu, Yuan; Jiang, Suihe; Song, Wenli; Huang, Hailong; Mao, Huahai; Wang, Hui; Liu, Xiongjun; Wang, Xianzhen; Lu, Zhaoping
ABSTRACT: Characteristics of deformation-induced transformation under loading dictate the mechanical performance of TRIP (transformation-induced plasticity)-reinforced bulk metallic glass composites (BMGCs), which have shown great potential as engineering materials. Here, we report that the addition of 0.3 at.% Ta in the T i 45 C u 41 N i 9 Z r 5 alloy could induce the formation of uniform glassy composite structure with B2-(Ti, Zr)(Ni, Cu) precipitates. More interestingly, nanosized A2-(Ti, Zr)(Ni, Cu) particles also formed inside B2 grains which effectively impede rapid propagation of martensite plates and lead to the formation of multi-oriented martensites, eventually homogenizing the involved plastic flow during deformation-induced transformation. Consequently, high fracture strength (∼3000 MPa), large plasticity (∼25%) and pronounced work-hardening ability were achieved. GRAPHICAL ABSTRACT: Impact statement: Microalloying of Ta not only homogenizes the B2 distribution, but also facilitates formation of multi-orientated martensites during deformation, resulting in simultaneously enhanced strength and plasticity of a Be-free Ti-based BMGC.